De Francia a San Luis Potosí. Circulación de conocimientos y lecturas locales en la segunda mitad del siglo XIX - Rangel Silva, José Alfredo (El Colegio de México, A.C., 2022)
In 1897, Wistano Luis Orozco, a lawyer specializing in agrarian law, published the pamphlet Las Aguas Subterráneas in San Luis Potosi. A manual for locating springs, it was inspired by an 1856 treatise from France, written by Abbé Paramelle. This article explores the circulation of knowledge and its adaptation to local contexts through an analysis of the reading and critical reception of the French text in Spain and Mexico, taking Orozco’s pamphlet as representative of the scientific-intellectual world of Mexican professionals in the late nineteenth century. Besides texts on geology and hydrogeology in Spanish, English and French, this article also makes use of contemporary periodicals as primary sources.